Children's rights in Croatia: Parental perspective - Keresteš, Gordana (2003)
A sample of 428 school-aged children, 242 mothers and 197 fathers completed questionnaires about knowledge, attitudes and perception of the level of realization of children's rights in Croatia. The present study deals with the data obtained from parents. Analyses revealed that although most of the parents had basic knowledge about children's rights, they were relatively poorly informed about the existence of specific legal documents regulating those rights. Most parents also believe that nowadays children have enough rights. However, all but few parents agree that children should be informed about their rights, considerenig themselves and school as the most responsible agents in that education. School and parents were also seen as main protectors in a case of violation of children's rights. For none of the 12 categories of children's rights and/or needs that were examined, parents believe that is fully realized. Family and government/state were seen as equally responsible for realization of nine of those 12 categories of rights/needs, while for three of them family was considered completely responsible. Importance of the obtained results in designing actions aimed at promotion of children's rights is discussed.
Projekt MZOS
ENG